2017
DOI: 10.1371/journal.pone.0181363
|View full text |Cite
|
Sign up to set email alerts
|

Obliteration of bacterial growth and biofilm through ROS generation by facilely synthesized green silver nanoparticles

Abstract: Mangifera indica inflorescence aqueous extract was utilized for production of green AgNPs. Synthesized AgNPs were characterized by UV-vis spectrophotometry, XRD, TEM, FESEM and particles size analyzer. AgNPs showed minimum inhibitory concentrations (MICs) of 8 μg ml-1 and 16 μg ml-1 for Gram negative (K. pneumoniae, P. aeruginosa and E. coli) and Gram positive (S. mutans and S. aureus) strains, respectively which was relatively quite low compared to chemically synthesized silver nanoparticles. AgNPs inhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(96 citation statements)
references
References 31 publications
4
90
0
2
Order By: Relevance
“…One of the important property of such nanoparticles is antimicrobial activity. Many green silver nanoparticles have been reported for antibacterial and antibiofilm activity through mechanisms like ROS generation (Qayyum et al, 2017). Also supportive studies on plant derived silver nanoparticles conclude that biogenic nanomaterials are biocompatible and an effective therapeutic agent against bacterial, fungal infections, and cancer treatment (Oves et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One of the important property of such nanoparticles is antimicrobial activity. Many green silver nanoparticles have been reported for antibacterial and antibiofilm activity through mechanisms like ROS generation (Qayyum et al, 2017). Also supportive studies on plant derived silver nanoparticles conclude that biogenic nanomaterials are biocompatible and an effective therapeutic agent against bacterial, fungal infections, and cancer treatment (Oves et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…[58]. Qayyum et al reported that AgNPs could induce bacterial cells to produce ROS, which might be the cause of cell lysis or distortion of bacterial membranes [59]. Therefore, it is rational to assume that antimicrobial activity of AgNPs can be ascribed to the damage of the cell membrane and the leakage of cytoplasm of Ao strain RS-2.…”
Section: Bacterial Cell Morphologymentioning
confidence: 99%
“…To improve the antimicrobial efficacy, an increasing number of novel silver materials have been developed . Silver nanoparticles (Ag NPs) are one of the most attractive material for catheter coatings [Fig.…”
Section: Antimicrobial Strategies For Urinary Cathetersmentioning
confidence: 99%
“…To improve the antimicrobial efficacy, an increasing number of novel silver materials have been developed. [38][39][40][41][42][43][44][45][46][47][48] Silver nanoparticles (Ag NPs) are one of the most attractive SCHEME 2. Mechanisms of bactericidal silver ion.…”
Section: Bactericidal Coatingsmentioning
confidence: 99%
See 1 more Smart Citation